The Argentine Folia suite. An encounter between the Hispanic legacy and Argentine folk music - Tolaba, Antonio Nicolás (2020)
This paper presents a resignification attempt of the harmonic-melodic scheme from the folia within the musical canons of Argentine folk dances and their musical genres. It contrasts their forms and sound parameters, and it analyses of both musical's repertoire universes. This study explores historical and musicological aspects of the Hispanic folia and contextual aspects of music creation in Argentina; such as nationalism, traditionalism, and nativism. Using these elements, a musical composition in suite form is proposed. This composition unites the harmonic-melodic scheme of the Hispanic folia and the musical forms of nine argentine folk dances.